Metasomatism of the Lithospheric Mantle Immediately Precedes Kimberlite Eruption: New Evidence from Olivine Composition and Microstructures - Cordier, Carole; Sauzeat, Lucie; Arndt, Nicholas T.; Boullier, Anne-Marie; Batanova, Valentina; Barou, Fabrice (Journal of Petrology, 2015)
International audience Most kimberlites contain abundant dunitic nodules. These are centimetre-sized, rounded and multi-grained assemblages of xenocrystic olivine with a wide range of compositions (Fo83 to Fo94). The absence of orthopyroxene and other mantle minerals and the range of olivine compositions have been attributed to reaction between mantle peridotite and (proto)kimberlitic fluid or melt, but the timing of the reaction is a subject of debate. In a kimberlite from the Kangamiut region of Greenland, nodule cores are surrounded by fine-grained outer margins with near-constant Fo contents (∼Fo88) but highly variable minor element contents (e.g. 500–2500 ppm Ni). These margins crystallized from the kimberlite melt and we show that their compositions can be explained by crystallization of olivine alone, if a high partition coefficient for Ni between melt and olivine (DNi > 20) is assumed. Orthopyroxene assimilation is not required, removing the constraint that its dissolution occurred during ascent of the kimberlite magma. Within some nodules, in addition to the usual core-to-margin gradients, we observe asymmetric compositional changes (variable Fo but near-constant minor element contents) across mobile grain boundaries. These changes document fluid percolation at the grain scale that occurred during dynamic recrystallization in the deforming lithospheric mantle. We note that chemical gradients associated with mobile grain boundaries are observed in olivines that cover the entire compositional range of the nodules, and propose that fluid-assisted dynamic recrystallization took place in dunite that was already compositionally heterogeneous. Reaction between peridotite and protokimberlitic melt or fluid and dissolution of orthopyroxene thus occurred within the lithospheric mantle, immediately (a few days) prior to the ascent of the kimberlite melt and the entrainment of the dunite nodules. We propose that the grain boundary zones probably mimic, at a fine scale, the fluid–peridotite interaction that ...